Augmented Modeling Activities to Support Conceptual Thinking in Physics - Bakari, Amina Zainab; Mensah, Daniel Kwame; Ngugi, Fatima Leila (International Journal of Technology and Modeling, 2023)
This article explores the implementation of augmented modeling activities as a pedagogical approach to enhance conceptual thinking in physics education. By integrating physical modeling with digital augmentation—such as simulations, augmented reality, or interactive visualization tools—students are encouraged to actively construct and revise mental models of physical phenomena. The study investigates how these hybrid modeling environments influence learners’ conceptual understanding, engagement, and problem-solving abilities. Drawing on classroom interventions and qualitative analysis, the findings suggest that augmented modeling not only makes abstract concepts more tangible but also promotes deeper reasoning, hypothesis testing, and collaborative learning. Implications for instructional design and the integration of technology in science education are discussed.